Homogenizacja kultury – utopia czy rzeczywistość? Krytyczne spojrzenie na tezę Francisa Fukuyamy - Nędzi, Ilona (Kultura-Społeczeństwo-Edukacja, 2025)
The idea of cultural homogenisation has been a topic of discussion among scholars since the existence of culture. However, it became more prominent with accelerated globalisation, marked by the rise of Western (American) culture. In this context, Fukuyama (1998) advanced the thesis that culture will ultimately become homogenised. To verify the researcher’s thesis and provide a critical view of the statements made by scientists, the analysis was based on the analysis of publications, scientific speeches, and verified press information. By demonstrating the fallibility of Fukuyama (1998), four aspects are presented: psychological, cultural dualism, cultural identity and legal. The psychological aspect demonstrates the necessity for positive experiences derived from travel, particularly exposure to unfamiliar cultures. The cultural dualism aspect underscores the simultaneous engagement with global culture while preserving distinctiveness. The cultural identity aspect highlights the strong sense of separateness within society, exemplified by the preservation of national or local identities, as seen in the case of Catalonia. The final aspect, the legal aspect, discusses the concepts of globalisation of law and global law, and finally questions them with the introduction of the concept of dualism of law. Based on observed legal processes in the world and analysis of literature, a new concept was introduced – dualism of law, naming this previously unnamed phenomenon. Consequently, it was determined that the hypothesis proposed by the researcher was erroneous, and a favourable trajectory for the advancement of global culture was delineated, orienting itself towards the cultural dualism that is extant in the business.